Population pharmacokinetic modeling of hydromorphone in cardiac surgery patients during postoperative pain therapy - Jeleazcov, Christian; Saari, Teijo I.; Ihmsen, Harald; Mell, Jan; Froehlich, Katharina; Krajinovic, Ljubica; Fechner, Jörg; Schüttler, Jürgen (Anesthesiology, 2014)
Hydromorphone is a µ-selective opioid agonist used in postoperative pain therapy. This study aimed to evaluate the pharmacokinetics of hydromorphone in cardiac surgery patients during postoperative analgesia with target-controlled infusion and patient-controlled analgesia.In this study, 50 adult patients were enrolled to receive intravenous hydromorphone during postoperative pain therapy. Arterial plasma samples were collected for measurements of drug concentration. Population pharmacokinetic parameters were estimated using nonlinear mixed-effects modeling. Results were validated and simulations were carried out to evaluate results.Data from 49 patients (age range, 40-81 yr) were analyzed. The pharmacokinetics of hydromorphone were best described by a three-compartment model. Age was incorporated as a significant covariate for elimination clearance and central volume of distribution. Scaling all parameters with body weight improved the model significantly. The final estimates of the model parameters for the typical adult patient (67 yr old, weighing 70 kg) undergoing cardiac surgery were as follows: CL1 = 1.01 l/min, V1 = 3.35 l, CL2 = 1.47 l/min, V2 = 13.9 l, CL3 = 1.41 l/min, and V3 = 145 l. The elimination clearance decreased by 43% between the age of 40 and 80 yr, and simulations demonstrated that context-sensitive half-time increased from 26 to 84 min in 40- and 80-yr-old subjects, respectively.The final pharmacokinetic model gave a robust representation of hydromorphone pharmacokinetics. Inclusion of age and body weight to the model demonstrated a significant influence of these covariates on hydromorphone pharmacokinetics. The application of this patient-derived population model in individualized pain therapy should improve the dosing of hydromorphone in patients undergoing cardiac surgery.
EVALuna2:16634